Hepatoprotective activity of methanolic extract of Malva parviflora against paracetamol-induced hepatotoxicity in mice (Bangladesh Journal of Pharmacology, 2014)
Malva parviflora (cheeseweed) is traditionally used as hepatoprotective. The current study was conducted to determine its hepatoprotective activity of aqueous methanolic extract of whole plant. Two doses of plant (250 mg/kg and 500 mg/kg) were administered in paracetamol intoxicated mice and results were compared with silymarin. Observational parameters were ALT, AST, ALP and total bilirubin. The results showed that the extract of M. parviflora produced significant (p